AN ANALYSIS OF PUMP POWER CALCULATION OF CONVERTED BANDUNG TRIGA REACTOR WITH PIPE ROUTING THROUGH DELAY TANK - Wardhani, Veronica Indriati Sri; Santoso, Budi (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2018)
The Bandung TRIGA 2000 Reactor has been widely used for conducting training, researches and isotop production since 1965. This reactor have to be decommissioned due no further fuelproduced by original vendor. Therefore, conversion of cylinder fuel into plate is needed. PT INUKI has been able to produce its own plate type fuel so that by changing the reactor core which was originally cylindrical into a square shape or converting the fuel element from cylindrical to plate type operation of the Bandung TRIGA 2000 reactor can be maintained for a long time. On this conversion, the reactor’s cooling system will change, which initially by natural convection to forced convection, while the direction of the cooling flow changes as well, which initially from bottom to top becomes from top to bottom. If the directional cooling flow of the plate TRIGA reactor system is made from top to bottom, without changing of piping, the result is a high exposure of Nitrogen-16 radiation on the surface of the reactor tank, therefore a delay tank is needed. By the new pipe routing system, it is necessary to reanalyze on determining the pump power requirements. The pump should be able to supply this energy. In other words, the total head produced by the pump must be equal to the total head required by the system. If the total system head data and coolant flow rate, and considering the efficiency of the pump and the motor drive pump have been analysed, so the pump power requirements can be calculated. The calculation result shows that the amount of pump power required to drain the cooling fluid in the primary system is 35 kW or 47 HP.